Effect of Melatonin Administration on Nerve Regeneration after Recurrent Laryngeal Nerve Injury - BILGEHAN CELIK; AHMET KARA; MEHMET GUVEN; SONGÜL DOGANAY; ÖZCAN BUDAK; EBRU M. GUVEN; TUNCAY COLAK; AHMET F. ERDEM; MAHMUT S. YİLMAZ (Anais da Academia Brasileira de Ciências)
Abstract Recurrent Laryngeal Nerve (RLN) injury is a complication in neck surgery. The aim of this study is to evaluate the effect of primary suture repair with melatonin treatment on nerve regeneration after RLN damage. After the RLN damage, nerve repair was performed in the first and fourth groups. The third and fourth groups were given intraperitoneal melatonin therapy daily for six weeks. EMG was applied to all subjects and vocal cord movements were evaluated endoscopically. At the end of the sixth week, all subjects were sacrificed, and their larynx were examinedhistologically. Vocal cord paralysis (VCP) was observed in all subjects after RLN damage. In the sixth week, improvement was observed in the first and fourth group who underwent nerve repair, whereas none in the second and third group, who did not undergo nerve repair, improved. With EMG, the highest MUP was in the fourth group. Histologically, an increase in Schwann cells, a decrease in axon damage, and cytoplasmic vacuolization were in the fourth group. Myelin protein zero and Ki-67 staining were the most in the fourth group. In our study, laryngoscopic, electrophysiological and histopathological findings show that melatonin contributes to nerve healing but this could not translate into functional recovery.